Radiofrequency ultrasound data acquisition with a 640-element array transducer for strain imaging: Experimental results with phantoms and biological tissue samples - Brusseau, Elisabeth; Bernard, Adeline; Meynier, Cyril; Ferin, Guillaume; An Nguyen-Dinh; Basset, Olivier (Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Annual International Conference, 2017)
This paper presents ultrasound elastography results obtained with a 640-element array transducer we have recently developed. This probe allows the acquisition of series of three adjacent imaging planes over time and therefore makes possible the computation of 2-D elastograms, with consideration of out-of-plane motion. In this study, elastography experiments were conducted on phantoms and bovine tissue samples, and compression was manually applied to the media via the hand-held ultrasound transducer. The results obtained with the proposed data acquisition and 3-D processing are presented and compared to those from a classical 2-D approach.